The «Novo Cinema Galego». Galiza on the path of the vanguard - Suárez, Pablo (Madrygal. Revista de Estudios Gallegos, 2014)
The main object of this article is making an approach to cinematography movements of last years, particularly to the question posed in Galiza around the “Novo Cinema Galego” concept –name of a wave with difficult delimitation, as we will see–, and make it in an explanatory way, establishing its causes, its origin and its evolution.